2015
DOI: 10.4103/0019-5545.161480
|View full text |Cite
|
Sign up to set email alerts
|

The Indian "girl" psychology: A perspective

Abstract: India has one of the fastest growing youth populations in the world. Girls below 19 years of age comprise one-quarter of India's rapidly growing population. In spite of India's reputation for respecting women, to an extent to treat her as a goddess, the moment a baby is born, the first thing comes to mind is “boy or girl?” as the differences are beyond just being biological. This article examines the significance of various psychological constructs and psychosocial issues that are important in the life of a “g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…Our contextual data provides pointers to a sex-differential pattern in the snakebite mortality which needs to be understood further within the socio-cultural context of Indian females to prevent and to treat snakebites in females. [ 47 , 48 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our contextual data provides pointers to a sex-differential pattern in the snakebite mortality which needs to be understood further within the socio-cultural context of Indian females to prevent and to treat snakebites in females. [ 47 , 48 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ignorance of legal rights by a girl also leads to issues like exposure to domestic violence, economic dependence, low self-esteem, no rights on property, denial of decision making rights, child immoral trafficking and exposure to sexually transmitted diseases, etc. (Rao, Vidya, and Sriramya 2015)…”
Section: Discussionmentioning
confidence: 99%
“…(Ministry of WCD Government of India 2017) Apart from this, government has taken many steps to remove the gender bias towards a girl child, like reservation of seats in technical education, legislative assemblies of parliament, government jobs, etc. (Rao, Vidya, and Sriramya 2015)…”
Section: Discussionmentioning
confidence: 99%
“…These young women are caught up in a cycle of economic dependence and fear for their own and their children’s lives, apart from being ignorant of their legal rights, lacking self-confidence and succumbing to family pressure. The sanctity of family privacy makes the authorities concerned reluctant to intervene and causes the women in question to deny the abuse (Gaffney-Rhys, 2010; Hampton, 2010; Rao et al, 2015). The International Centre for Research on Women conducted a study in two Indian states and found that girls married before the age of 18 were two times more likely to report being beaten, slapped or threatened by their husbands than those who married later (Kanesathasan et al, 2008).…”
Section: Victimization In Child Marriagementioning
confidence: 99%